2021
DOI: 10.3390/s21030741
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the ATMOS41 All-in-One Weather Station for Weather Monitoring

Abstract: Affordable and accurate weather monitoring systems are essential in low-income and developing countries and, more recently, are needed in small-scale research such as precision agriculture and urban climate studies. A variety of low-cost solutions are available on the market, but the use of non-standard technologies raises concerns for data quality. Research-grade all-in-one weather stations could present a reliable, cost effective solution while being robust and easy to use. This study evaluates the performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…This is in agreement with other findings that have shown that meteorological parameters measured from a ground station can compare relatively well with other observations from a reference source e.g. AWS (Dombrowski et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with other findings that have shown that meteorological parameters measured from a ground station can compare relatively well with other observations from a reference source e.g. AWS (Dombrowski et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Whereas the surface pressure was highly correlated between the three stations, some studies have found uncertainties in the comparisons between on ground station pressure and the reference data, e.g. (Dombrowski et al, 2021). The high variability between some meteorological variables at different stations could be due to several factors such as instrument error, change of location, damages or lack of station maintenance (Ford et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Particular focus should be laid on high precipitation intensities occurring in tropical regions. Dombrowski et al [17] report about relatively large biases for precipitation and wind speed. Further work should focus on the performance assessment of the ATMOS 41 during extreme precipitation and wind speed as well as the long-term durability and accuracy of the station.…”
Section: Introductionmentioning
confidence: 99%
“…Intelligent agriculture, based on Internet of Things (IoT) technologies, allows farmers to reduce waste and increase productivity, from irrigation with greater precision to the amount of fertilizer used [2]. In addition, it can help prevent pollution [3], monitoring climatic conditions at low cost [4], and bring solutions by adding artificial intelligence methods [5,6].…”
Section: Introductionmentioning
confidence: 99%